Characterization of the Immune Cell Infiltration Profile in Pancreatic Carcinoma to Aid in Immunotherapy - Luo, De; Kuang, Fei; Du, Juan; Zhou, Mengjia; Peng, Fangyi; Gan, Yu; Fang, Cheng; Yang, Xiaoli; Li, Bo; Su, Song (Frontiers in Oncology, 2021)
The tumor microenvironment (TME) is comprised of tumor cells, infiltrating immune cells, and other stromal components. Multiple publications have demonstrated that the immune cell infiltration (ICI) in TME is strongly correlated with responsiveness to immunotherapy and prognosis of several cancers. However, the ICI profile of pancreatic carcinoma (PC) still remains unclear. Here, we employed two algorithms to characterize the ICI profile of PC patients. Based on our results, we identified 2 ICI patterns and calculated ICI score, using principal component analysis. We revealed a better prognosis in patients with low ICI score. Moreover, we found that low tumor mutation burden (TMB) resulted in better overall survival than high TMB. In this study, a high ICI score referred to elevated PD-L1/TGF-β levels, reduced immune-activation-related genes expression, and activation of the cell cycle pathway, along with DNA repair pathway. We also demonstrated that metabolism signaling pathways were inhibited in low ICI score group. These data may explain why a high ICI score equates to poor prognosis. Based on our analysis, ICI score can serve as an effective predictor of PC prognosis. Assessing ICI profile, among a large patient population, will not only enhance our knowledge of TME, but also aid in the development of immunotherapies for PC.